Organization of Financial Reporting in Accordance with Requirements of the IFRS Taxonomy - V. Сhebanova, N.; I. Yefimenko, T.; M. Orlova, V.; N. Korolova, N. (International Journal of Engineering and Technology, 2018)
The authors of the article exposed the methodical questions of introduction, new for the registration process of Ukraine of the phenomenon. It is taxonomy of the financial reporting (ТFR). At the same time continued consideration of questions of the use of the financial reporting for the acceptance of administrative decisions.Essence of ТFR is exposed in the context of classification and systematization of ingredients of the financial reporting. It in itself informative system and connections between the constituents of such system. Authors suggested to attribute ТFR to the mathematical determined models. The construction of such models  requires the clear plan of actions in three steps: a mathematical model - an algorithm of calculation - computer program. The purpose of researches: of one times  to prove that introducing in economic science of exact knowledge, enables to limit the intuitional acceptance of administrative decisions and extend the limits of application of rational methods. It will be realized on condition of the use of different methods, methods and approaches - from nonlinear, stochastic models to the modern  programming languages .
Keywords: administrative decision; financial reporting; informative model of enterprise; record-keeping; taxonomy.